"To be in the institution but not of it" : tentatives et réflexions pour une histoire queer de l'art, en compagnie d'Andrea Geyer, de Rashid Johnson et de Sherrie Levine - Dumaine Allard, Philippe (Université du Québec à Montréal, 2017)
Cette recherche s'intéresse à l'ouverture d'une perspective queer en histoire de l'art qui se caractérise par une inscription trouble à l'intérieur et à l'extérieur de l'académie. Tout d'abord, je tente d'y démontrer que les savoirs dits officiels et les histoires (de l'art) canoniques sont construits sur des processus de sélection et d'exclusion qui reproduisent des inégalités sociales. Face à ce constat, j'explore, à travers les écrits d'un grand nombre d'auteur.e.s queers, féministes et racisé.e.s, des postures résistantes aux savoirs dominants. En me penchant sur la question d'un temps queer, il s'agit de penser des relations dynamiques au passé, au présent et au futur. Or face à ma propre difficulté à compléter l'exercice en cours, ce mémoire réfléchit aux inévitables achoppements qui marquent le développement de savoirs critiques dans les institutions. En ce sens, l'échec devient ici partie prenante d'une posture queer qui s'inscrit non seulement en résistance face aux idées véhiculées par les savoirs dits officiels, mais qui cherche aussi à repenser les structures et modes d'écriture usuels des travaux savants. Affichant une méthodologie de la conversation, ce mémoire s'attarde à lire les œuvres de Sherrie Levine, d'Andrea Geyer et de Rashid Johnson à la lumière des idées d'auteur.e.s varié.e.s et, en échange, à voir dans ces œuvres des modèles pour penser autrement l'organisation des savoirs. Privilégiant la multiplication des voix au confort de la synthèse, ce mémoire donne chair à une pensée en flux, organisée selon une logique de renvoi d'idées. Il trace les contours flous d'une posture queer en histoire de l'art qui se définirait par son caractère indéfinissable, une posture qui fait de la mouvance une stratégie de résistance. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : queer, savoirs dominants, temporalités alternatives, échec
Keywords: IREF; approches et analyses; discipline; discours dominant; histoire de l'art; identités LGBTQIA2+; inégalités; mémoires/thèses; queer; ressource en ligne; savoirs dominants; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques